Retail Payment Costs and Savings in Kosovo - World Bank; Central Bank of Kosovo (CBK) (World Bank, Washington, DC: Central Bank of Kosovo, Prishtinë, Kosovë, 2022)
This report is based on a study of the costs of retail payments in Kosovo, using a methodology (A Practical Guide for Measuring Retail Payment Costs) developed by the World Bank's Payment System Development Group (PSDG), part of the Finance, Competitiveness, and Innovation Global Practice. The study is based on survey data, with questionnaires administered to a sample of households and businesses on the demand side, as well as to 9 commercial banks operating in Kosovo; the Central Bank of Kosovo (in its role as currency issuer and as the operator of the Automated Clearing House); 4 money transfer operators; and the Post Office on the supply side. The study aims to establish a sound economic baseline for the national retail payments system regarding the costs of different payment instruments to better guide system development and enable high-impact changes. Efficiency gains resulting from migration to lower-cost retail payment instruments and more efficient use of those instruments could have significant benefits for economic development and growth as the transaction costs of exchanging goods and services are reduced. Lower costs of retail payments can also fundamentally extend the access of electronic payment services to lower-income households and further improve the efficiency of the national payments system as access to modern payment instruments is broadened.